English as a Foreign Language Teachers’ Well-Being, Their Apprehension, and Stress: The Mediating Role of Hope and Optimism - Yang, Hui-min (Frontiers in Psychology, 2022)
Studies have shown that teachers’ well-being has a positive effect on teachers’ learning quality and learners’ performance. Nevertheless, teaching is a stressful and exhausting profession at all academic level with special difficulties about the nature of language education. Tension and fear are still classic challenges in learning, though the concepts such as hope and optimism are core issues in assisting teachers to feel happy during instruction and work longer. The present review makes efforts to provide the most current confirmation on the interface of hope and optimism with educational issues since they are progressively documented as significant emotional capitals for educational success, job growth, and presentation. It is worth mentioning that the current review of research can benefit educational administrations, and other stakeholders and officials in the educational community to contemplate the functions of constructive emotions in the process of learning to decrease and even diminish stress and apprehension that consequently lead to flourishing.